Pengaruh Media Interaktif Educaplay terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas V SD - ikhwaturraiyuna ikhwaturraiyuna; Waliyul Maulana Siregar; Apiek Gandamana; Winara Winara; Khairul Usman (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to determine the effect of the Educaplay interactive media on Pancasila education learning outcomes for the topic “Cultural Diversity in My Indonesia” among fifth-grade students at SDN 104203 Bandar Khalipah in the 2025/2026 academic year. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The study population consisted of all 46 fifth-grade students, with the sample comprising Class VA (23 students) as the experimental group and Class VB (23 students) as the control group. Data analysis techniques included a normality test (Shapiro-Wilk), a homogeneity test (Levene), and a hypothesis test (Independent Sample t-test) using SPSS version 27. The results showed that the mean posttest score for the experimental class (83,91) was higher than that of the control class (76,74). The learning achievement rate for the experimental class reached 95,65%, while that of the control class was only 78,26%. The hypothesis test results yielded a calculated t-value of 2,661 with a significance level (2-tailed) of 0,011 < 0,05; therefore, H₀ was rejected and Hₐ was accepted.